The Role of Supervision and Education Authorities of Youth Culture Rovinsigorontalo in School Service - Talha Dangkua; Srihandayani Suprapto (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This study aims for this study to see the role of supervision of the Gorontalo Province Youthand Sports Education Officeinthe School System Servicesat SMKN 1 Limboto. This study uses a descriptive method with a qualitative approach. The results showed that the supervisory role carried out by the Department of Education, Culture, Youth and Sports was not maximally implemented. The role of the Youth and Sports Education Office, Culture, needs to be improved, especially interms of monitoringtheschoolservice system to improve the quality of education, especially in terms of improving human resources. This is often seen in the sub-optimal quality of the teaching staff's human resources, in addition to the lack of intense supervision of the school service system processbythe Gorontalo Province Youth and Sports Education Office, Culture, especially in Vocational High Schools